CONTRIBUTIONS OF DM EMI TO LOWER FREQUENCY RANGE OF RADIATED EMISSIONS IN A BUCK CONVERTER - M.L.Sudheer, Shantala, (Design Engineering, 2021)
Conducted Electromagnetic Interference (EMI) Emissions from Switched Mode Power Supplies (SMPS) add to the Radiated Emissions from it due to Differential Mode and Common Mode noise currents. This may go beyond the EMC's established limits, as well asinternational norms. The Common Mode circulating noise currents will contribute the most to the Radiated Emissions. On the other hand, Differential Mode noise currents will contribute to Radiated Emissions as well, but not to the same amount as Common Mode Noise Currents. This paper examines the contribution of conducted DM noise to the Radiated Emission from a buck converter. LTSpice was used to simulate a buck converter that was modelled with the Line Impedance Simulation Network (LISN). Simulated conducted DM noise was obtained for various switching frequency. The DM Noise currents' spectrum reveals that they also contribute to Radiated Emissions in the 30 MHz to 120 MHz lower frequency region. This was tested for several Buck converter Switching Frequencies. In the whole 30 MHz frequency range to 3 GHz, the CM Noise currents are the largest contributors to the Radiated Emissions. The DM noise currents were studied up to a frequency range of 30 MHz to 120 MHz in this study. Beyond 120 MHz, there was no significant contribution of DM noise currents to the Radiate Emissions in the Buck converter studied, Noise currents flowing in LISN produce radiated noise as a result of this DM conducted EMI. Simulation studies and their radiation at a 3m radius are measured using mathematical methods. This can be used to create Filter circuits that lower the amount of noise to compliant levels.